Key Role of Microglial Matrix Metalloproteinases in Choroidal Neovascularization - Kim, Juhee; Kim, Jong-Heon; Do, Ji Yeon; Lee, Jung Yi; Yanai, Ryoji; Lee, In-kyu; Suk, Kyoungho; Park, Dong Ho (Frontiers in Cellular Neuroscience, 2021)
Age-related macular degeneration (AMD), especially neovascular AMD with choroidal neovascularization (CNV), is the leading cause of blindness in the elderly. Although matrix metalloproteinases (MMPs) are involved in pathological ocular angiogenesis, including CNV, the cellular origin of MMPs in AMD remains unknown. The present study investigated the role of microglial MMPs in CNV. MMP activities were analyzed by gelatin zymography in aqueous humor samples from patients with CNV and laser-induced CNV mice. Active MMP-9 was increased in the aqueous humor samples from neovascular AMD patients compared with control subjects. In the retinal pigment epithelium (RPE)/choroid from CNV mice, active MMP-9 increased, beginning 1 h post-CNV induction, and remained upregulated until Day 7. In RPE/choroid from CNV mice, active MMP-9 was suppressed by minocycline, a known microglial inhibitor, at 6 h and 1 day post-CNV induction. Flow cytometry revealed that the proportion of activated microglia increased very early, beginning at 1 h post-CNV induction, and was maintained until Day 7. Similarly, immunohistochemistry revealed increased microglial activation and MMP-9 expression on CNV lesions at 6 h and 1 day post-CNV induction. SB-3CT, an MMP inhibitor, decreased vascular leakage and lesion size in laser-induced CNV mice. These findings indicated nearly immediate recruitment of activated microglia and very early MMP-9 activation in the RPE/choroid. These regulatory mechanisms could contribute to CNV development, and modulation of microglial MMPs is thus a novel putative therapeutic modality for neovascular AMD.